Phytochemical Constituents of Crotalaria pallida Ait. Leaf Extract and Effects on Uterus and Serum Lipid Profiles of Ovariectomized Rats - พร้อมพรม, ผู้ช่วยศาสตราจารย์ ดร.วิลาวัณย์; ชาแท่น, ผู้ช่วยศาสตราจารย์ ดร. วรรณชัย (Journal of Food Health and Bioenvironmental Science, 2019)
The aim of this study was to investigate active components of an ethanolic leaf extract of Crotalaria pallida by GC-MS and to study the effects of leaf extracts on uterine weight, uterine tissues and serum lipid levels. Ovariectomized Sprague Dawley rats were administrated with C. pallida leaf extracts at different doses (250 and 500 mg/kg body weight). These rats were treated for 14 days. Fourteen phytochemical constituents were identified, and the major chemical constituent that could be identified was 9,12,15- octadecatrienoate (C20H34O2). C. pallida leaf extracts at both doses could not increase uterine weight when compared with normal rats and ovariectomized rats treated with 17α -ethyl estradiol. In the histological study of uteri, the two doses of plant extracts could not increase endometrial epithelium cells of ovariectomized rats. However, the leaf extracts at the dose of 500 mg/kg body weight decreased low-density lipoprotein when compared with the OVX group (P<0.05). These results indicate that the leaf extract from C. pallida could decrease low-density lipoproteins of ovariectomized rats